Characterization of antibodies for quantitative determination of spiggin protein levels in male and female three-spined stickleback (Gasterosteus aculeatus) - Karlsson Johnny; Hoffmann Erik; Liimatta Harri; Scherbak Nikolai; Berg Håkan; Olsson Per-Erik (BMC, 2009)
Abstract Spiggin is an adhesive glycoprotein produced in the kidney of sticklebacks during the breeding season and is subsequently secreted into the urinary bladder from where it is employed for nest building. Since the production of the protein has been shown to be under androgenic control, spiggin has been suggested to be a useful biomarker for androgenic substances in the environment. In this study, two polyclonal spiggin antibodies based on synthetic peptides and one polyclonal antibody directed against native spiggin have been characterized. The antibodies ability to identify spiggin was investigated by quantitative immunoassay. For both peptide antibodies the quantification range was determined to be between 1 and 80 ng spiggin and determination of renal spiggin levels from immature and mature males displayed a 15-fold increase in total spiggin content of the kidney resulting in a 6-fold increase in male kidney weight due to hypertrophy. The kidney somatic index (KSI) was found to correlate well with the total renal spiggin content and therefore it appears that KSI in sticklebacks could be used as an initial method to identify substances displaying androgenic effects. Furthermore, western blot analysis revealed that the polyclonal antibodies recognize different spiggin isoforms and that spiggin can be detected in the urinary bladder and kidney of both males and female sticklebacks. In order to develop a quantitative detection method for native spiggin it is necessary to produce a standard that can be used in a bioassay. Due to the adhesive and polymerization characteristics of spiggin the protein is difficult to use as a standard in bioassays. So far spiggin has been shown to exist in at least 14 isoforms, all of which contain polymerization domains. To overcome the solubility problem we have produced recombinant spiggin gamma, with only one polymerization domain, that can be expressed in E. coli. Western blot analysis demonstrated that the polyclonal antibodies were able to detect recombinant spiggin gamma protein in bacterial cell lysate, suggesting that it may be developed into a useful source of standard spiggin to be used for quantitative determination of androgen induced spiggin production in sticklebacks.